2019
DOI: 10.1186/s13643-019-1014-8
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence influencing factors—an (updated) overview of systematic reviews

Abstract: Background Non-adherence negatively affects the efficacy, safety and costs of therapies. Non-adherence is a multifactorial problem. This systematic review (SR) of SRs (overview) aims to identify factors that can influence the adherence of adult patients with chronic physical diseases. Methods We performed a systematic literature search in MEDLINE and Embase on June 13, 2018. We included SRs on the factors that can influence adherence in adult patients taking oral medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
245
3
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(277 citation statements)
references
References 44 publications
18
245
3
11
Order By: Relevance
“…Both Laba et al and Al‐Ganmi et al also found no correlation with non‐adherence and therapy‐related factors . These are consistent with findings from the review by Gast and Mathes which found mostly no impact on adherence by therapy intake regimen . However, our study found a weak but statistically significant correlation between non‐adherence and the number of prescribed medicines, non‐prescription medications and total number of medications.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Both Laba et al and Al‐Ganmi et al also found no correlation with non‐adherence and therapy‐related factors . These are consistent with findings from the review by Gast and Mathes which found mostly no impact on adherence by therapy intake regimen . However, our study found a weak but statistically significant correlation between non‐adherence and the number of prescribed medicines, non‐prescription medications and total number of medications.…”
Section: Discussionsupporting
confidence: 91%
“…This study found a weak but statistically significant correlation between the number of missed doses and the patient's age, level of education and employment status. Similar to this, reviews of non‐adherence literature have found an association with age, education and employment . In contrast, Australian studies by Laba et al and Al‐Ganmi et al found no significant correlation between non‐adherence and demographic factors .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although a number of systematic reviews have been conducted that aimed to identify factors that can influence medication adherence, including illness perceptions, specific medication beliefs, as well as culture and the demographic factors [ 6 , 17 , 18 , 19 ], none of these have explored the relationship between general beliefs about medicine determined through the BMQ and medication adherence of patients with chronic diseases such as HTN, COPD, asthma, and DMT2.…”
Section: Introductionmentioning
confidence: 99%
“…В работе Khan MU и Aslani P [10], как и в исследовании АНТЕЙ, было выявлено, что к значимым факторам, влияющим на приверженность, относятся стоимость лечения и опасение развития ПЭ ЛП. В то же время, в систематическом обзоре Gast A и Mathes T [11] влияние на приверженность ПЭ ЛП не подтвердилось, что, вероятно, связано с описываемыми авторами ограничениями данного обзора -отсутствием анализа факторов, связанных с терапией, в связи с чем полученные результаты могли быть неполными.…”
Section: Discussionunclassified